2015
DOI: 10.1111/pace.12654
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implantable Cardioverter Defibrillators on Survival of Patients with Centrifugal Left Ventricular Assist Devices

Abstract: The benefit of ICD therapy in the setting of continuous flow LVAD therapy is uncertain. Although prolonged ventricular arrhythmias (VAs) may potentially impact on patient survival, LVAD therapy is beneficial in prevention of sudden cardiac death due to VAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 26 publications
1
12
0
2
Order By: Relevance
“…Studies with primarily pulsatile LVADs have demonstrated a mortality benefit associated with ICDs during LVAD support (6,7); however this finding has not been replicated with continuous-flow LVADs (CF-LVAD). (8-10) Two recent meta-analyses using similar data (292 patients shared) have shown a non-statistically significant trend towards decreased mortality associated with ICD use in CF-LVAD patients: one with 361 patients with a CF-LVAD (68% with an ICD, RR: 0.76; 95% CI: 0.51-1.12) (11) and the other with 292 patients (70% with an ICD, OR 0.63, 95% CI 0.33–1.18). (12) This study sought to determine if the presence of an ICD provided a mortality benefit during CFLVAD support as a bridge to transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with primarily pulsatile LVADs have demonstrated a mortality benefit associated with ICDs during LVAD support (6,7); however this finding has not been replicated with continuous-flow LVADs (CF-LVAD). (8-10) Two recent meta-analyses using similar data (292 patients shared) have shown a non-statistically significant trend towards decreased mortality associated with ICD use in CF-LVAD patients: one with 361 patients with a CF-LVAD (68% with an ICD, RR: 0.76; 95% CI: 0.51-1.12) (11) and the other with 292 patients (70% with an ICD, OR 0.63, 95% CI 0.33–1.18). (12) This study sought to determine if the presence of an ICD provided a mortality benefit during CFLVAD support as a bridge to transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with severe stage D systolic heart failure necessitating LVAD therapy have ICDs implanted before their LVAD surgery. Although ICD therapy has not been conclusively shown to provide mortality benefit in LVAD patients, 6 , 7 owing to the high incidence of ventricular arrhythmias, 8 , 9 therapies including shocks are programmed in most patients. Recently, an increasing number of LVAD patients have been reported to present with multiple ineffective ICD shocks.…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenlerle sol ventrikül destek cihazları ventriküler aritmileri azaltmamaktadır ve hatta arttırma potansiyeline sahiptirler. [328,330] Aritmiler sağ kalp fonksiyonlarını bozarlar, pompa debisini düşürebilirler ve kalp yetersizliği semptomlarına neden olabilirler. Ancak ventriküler fibrilasyon ve asistol gibi hayatı tehdit edici bir aritmide dahi cihazın debisi nedeniyle hasta asemptomatik kalabilir.…”
Section: C) Aritmiunclassified
“…[331] Ventrikü-ler aritmiler cihaz olgularında ani ölüm nedeni değil-dirler ve ICD'nin sağ kalıma olumlu bir etkisi yoktur. [330] Ancak ciddi ventriküler ve atriyal aritmiler sağ kalp fonksiyonlarına olumsuz etkileri nedeniyle tedavi edilmelidirler. Mevcut Uluslararası Kalp Akciğer Nakli Derneği (International Society for Heart and Lung Transplantation, ISHLT) kılavuzu bu hastaların ICD reaktivasyonunu implantasyon sonrasında önermekte-dir.…”
Section: C) Aritmiunclassified